The cuff leak test in critically ill patients: An international survey of intensivists. Issue 8 (16th June 2021) - Lewis, Kimberley; Almubarak, Yousef; Hylander Møller, Morten; Jaeschke, Roman; Perri, Dan; Zhang, Ying; Du, Bin; Nishida, Osamu; Ntoumenopoulos, George; Saxena, Manoj; Truwit, Jonathon; Young, Paul J.; et al.
Abstract: Background: The cuff leak test (CLT) is used to assess laryngeal edema prior to extubation. There is limited evidence for its diagnostic accuracy and conflicting guidelines surrounding its use in critically ill patients who do not have risk factors for laryngeal edema. The primary study aim was to describe intensivists' beliefs, attitudes, and practice regarding the use of the CLT. Methods: A 13‐item survey was developed, pilot‐tested, and subjected to clinical sensibility testing. The survey was distributed electronically through MetaClinician®. Descriptive statistics and multivariable regression analysis were performed to examine associations between participant demographics and survey responses. Results: 1184 practicing intensivists from 17 countries in North and South America, Europe, Oceania, and Asia participated. The majority (59%) of respondents reported rarely or never perform the CLT prior to extubating patients not at high risk of laryngeal edema, which correlated with 54% of respondents reporting they believed a failed CLT did not predict reintubation. Intensivists from the Middle East were 2.4 times more likely to request a CLT compared to those from North America. Intensivists with base training in medicine or emergency medicine were more likely to request a CLT prior to extubation compared to those with base training in anesthesiology. Conclusion: Use of the CLT prior to extubating patients not at high risk of laryngeal edema in the intensive care unit is highly variable. Practice appears to be influenced by country of practice and base specialty training.